Low rate of clinically important avascular necrosis of the femoral head after Ludloff's procedure. Issue 3 (May 2018) - Holbeck-Brendel, Jesper; Møller-Madsen, Bjarne; Hvid, Ivan; Hellfritzsch, Michel B; Pedersen, Line K; Dalsgaard, Peter; Rahbek, Ole
Introduction: Ludloff's procedure for open reduction of congenital dislocation of the hip (CDH) is recommended for its minimal tissue damage, but is criticised for the risk of late avascular necrosis (AVN) of the femoral head. The aim of present study was primarily to assess the risk of late AVN of the femoral head and secondly the range of motion (ROM) of the hip and the quality of life in children following Ludloff's procedure. Methods and materials: 13 hips in 11 children after Ludloff's procedure due to CDH were included retrospectively from 1997 to 2005 at Aarhus University Hospital. Radiographs were evaluated for the presence of AVN of the femoral head and classified according to the Bucholz and Ogden classification, with type 2-4 having clinical relevance. A clinical examination included range of motion (ROM) and leg length discrepancy (LLD) measurements. The HAGOS hip questionnaire evaluated activity, participation and quality of life. Results: No severe type 3-4 AVN was observed. 2 type 2 and 5 type 1 were observed. AVN was observed in 7 of the 13 operated hips (54%). An 8.6° difference in flexion for unilaterally treated hips was observed (p<0.02). 8 of 11 patients had minor LLD (range 0.5-2 cm). Conclusions: Only minor AVN of clinical importance was seen after Ludloff's procedure.